Globalizace a krize v souvislostech - Brychtová, Šárka (Univerzita Pardubice, 2013)
Submitted article is attempt about not only uneconomic look on present-day economic crisis and globalized world. The present crisis, however with different attribute, is probably result of the concourse of several processes among what surely belong globalization and contextual high flexibility of employment market, crisis of welfare state, social system or various forms of de-solidarity… Development of the society can be pointed at social and cultural regress and probability that it will be such way is high. Views of the modern society development and its solution vary from each other very much. Does existed alternative then alternation of thinking of human and society?
Globalization and crisis in connection
Keywords: economic crisis; globalization; public sector; concentration of power; transformation of thinking and society; causes of crisis; way from crisis; balance